Modern principles of the radiation protection from sources of ionizing radiation in medicine. Part 2: radiation risks and development of the system of radiation protection - G. G. Onischenko; A. Yu. Popova; I. K. Romanovich; A. V. Vodovatov; N. S. Bashketova; O. A. Istorik; L. A. Chipiga; I. G. Shatsky; S. S. Sarycheva; A. M. Biblin; L. V. Repin (Радиационная гигиена)
According to the Decree of the President of the Russian Federation №585, 13.10.2018, the main approaches to the provision of the radiation safety of the public of the Russian Federation from the use of the sources of ionizing radiation in medicine are the harmonization of the national legislative documents with the international recommendations and the development of the new and improvement of the existing methods of the assessment of the individual patient doses and corresponding radiation risks. The current study was aimed at the justification of the complex of actions to prevent the unnecessary medical exposure of the Russian population. That required to analyze the existing national and international approaches to the assessment of the radiation risks from medical exposure and the results of the existing epidemiological studies, as well as to assess the risks from the most common and/or high dose X-ray examination (computed tomography, interventional examinations, nuclear medicine) for pediatric and adult patients. It was indicated, that these examinations correspond to the “Low” and “Moderate” radiation risk categories. The level of the lifetime radiation risk of cancer morbidity in the Russian Federation for the computed tomography was estimated as 1 case per 3-30 thousand examinations. The performed analysis of the existing international regulatory and methodical documents indicated the significant differences in the practice of the radiation protection in medicine. International practice is mainly based on the practical application of the principle of justification by using the X-ray examination referral guidelines and various methods of risk communication with patients. Main actions to reduce the patient doses and to improve the diagnostic image quality are performed on the hospital level by medical physicists in collaboration with medical staff and representatives of the vendor. It should be noted that dose limits are not applied to the exposure of healthy individuals from screening X-ray examinations. Based on the results of the comparison of the national and international practices of the radiation protection in medicine, both general and specific (for different X-ray modalities) recommendations for the improvement of the system of the radiation protection of the patients and staff were developed. These recommendations should be implemented on practice in the form of the complex program of the optimization of the radiation protection of the public of the Russian Federation from medical exposure. This program can be developed and implemented through the collaboration of the Federal Service of Surveillance on Consumer Rights Protection and Human Well-being and the Ministry of Healthcare of the Russian Federation.